The completely mobilized remnant stomach: A new choice to reconstruct the esophagus in lower thoracic esophageal carcinoma with a history of distal gastrectomy. (September 2018) - Mao, Zhangfan; Wang, Bo; Dong, Ping; Huang, Jie
Abstract: Objective: It is a significant surgical challenge to reconstruct esophagus for the patients following distal gastrectomy (DGE). Remnant stomach seems to be a better choice compared with colon or jejunal. But many complicated surgical methods were performed because of limitation of feeding vessels. We found the remnant stomach remained viable when all the feeding vessels were dissected. We used the completely mobilized stomach to reconstruct esophagus successfully in 29 lower thoracic esophageal carcinoma patients with a history of DGE. Methods: The clinical data of 29 patients were retrospectively analyzed from August 2005 to March 2017 who accepted esophagoplasty by the completely mobilized remnant stomach. All the vessels of the remnant stomach were dissected including short gastric, posterior gastric, left gastric and left gastroepiploic vessels. The DGE included 2 Billroth I and 27 Billroth II. Result: No perioperative death, no remnant stomach necrosis occurred. One Leakage was the iatrogenic injury on the remnant stomach. The other postoperative complications were the pulmonary infection(5) and arrhythmia(4). Conclusion: The completely mobilized remnant stomach was viable and functional after dissecting all the feeding vessels. Application of it was a new and feasible surgical method to perform esophagoplasty with the simpler procedure and less complication. Highlights: It is a novel technique to reconstruct esophagus for gastrectomized patients. It is the maximum number of application of the technique. It is the first proof the blood supply of the completely mobilized remnant stomach. It makes the complicated surgical procedure simple. Application of the completely mobilized remnant stomach was reported rarely.